Analisis Manajemen Risiko Berbasis ISO 31000 pada Sanggar Kegiatan Seni Anak: Studi Kasus Sanggar Crayon - Lanina Pratiwi; Siska Amelia; Sanita Putri Yaperta; Ayesa Sofwa Aulia; Alfiana Alfiana (Indo Publishing, 2026)
This study examines the implementation of ISO 31000-based risk management at Sanggar Crayon, a children’s art studio. The studio faces operational, financial, marketing, human resources, and legal/administrative risks that may affect its operations and sustainability. Data were collected through in-depth interviews, field observations, and document analysis, then assessed using a Likelihood × Impact matrix. Findings indicate several high and very high-level risks requiring immediate mitigation, such as strengthening operational procedures, providing emergency funds, managing resources, and enhancing communication with instructors, parents, and suppliers. This approach enables effective risk control, minimizes negative impacts, and supports smooth operations, child safety, parental satisfaction, and the sustainability of Sanggar Crayon.